Policy and Voting Preferences of Romanian Migrants 2000-2016 - Burean, Toma (Political Preferences, 2018)
In most studies of voting behavior, political preferences are explained at the level of the “country, election, electoral cohort or individual voter” (Franklin 2004). Notably absent from these studies is the impact of voters living abroad. Their importance is not to be neglected, especially in democratizing states. This research targets the predictions that lie behind the turnout and preferences of Romanian emigrants. Romanian Diaspora consistently votes for parties and candidates that promise reforms. This vote is associated with liberal economic policy preferences and support for minority groups. I test these hypotheses with elections results data from 2000 to 2016 coupled with data collected from Votulmeu.com an online Voting Advice Application from the 2012 parliamentary and 2014 presidential elections in Romania. Key words: emigrants, voting, policy preferences, Romania, Voting Advice Applications